Colonial Office Correspondence Relating To Brunei 'destroyed Under Statute' 1906–1934 - AVM Horton, AVM Horton (Penerbit Universiti Sains Malaysia (USM Press), 2005)
In this paper the author scans the registers of correspondence relating to Brunei (1906–34) held in the National Archives at Kew. An annotated checklist of documents is provided. It is concluded that useful data can be yielded; and that, in a case such as Brunei, where documentation is in short supply, no potential source of information should be neglected. The exercise raises issues about the preservation of historical records. Suggestions for further research are provided.